(untitled) (Materiali di Estetica. Terza serie, 2023)
The article collects the speech given at the Spinoza Seminar at the Fondazione Corrente, on January 17th, 2023, by the contemporary Italian-Belgian artist Lorenzo Gatti (1955), who over the years has created a series of large ‘maps’ dedicated to Baruch Spinoza’s work Ethica, ordine geometrico demonstrata (1677).